The β-Secretase Enzyme BACE1: A Biochemical Enigma for Alzheimer’s Disease - Shah, Hirak; Patel, Ashish; Parikh, Vruti; Nagani, Afzal; Bhimani, Bhargav; Shah, Umang; Bambharoliya, Tushar (CNS & Neurological Disorders - Drug Targets, 2020)
Beta site amyloid precursor protein cleaving enzyme 1 (BACE1) is a rational target in Alzheimer’s Disease (AD) drug development due to its role in amyloidogenic cleavage of Amyloid Precursor Protein (APP) in generating Amyloid β (Aβ). This β-secretase cleaves not only Amyloid Precursor Protein (APP) and its homologues, but also small series of substrates including neuregulin and β subunit of voltage-gated sodium channel that play a very important role in the development and normal function of the brain. Moreover, BACE1 is modulated at the post-translational level by several factors that are associated with both physiological and pathological functions. Since the discovery of BACE1 over a decade ago, medicinal chemistry and pharmacokinetics of BACE1 small molecule inhibitors have proven challenging for the treatment of Alzheimer’s disease.
Keywords: Alzheimer' s disease